Homosexuality in Greece and Rome : a sourcebook of basic documents (The Joan Palevsky imprint in classical literature, 2003)
Important primary texts on homosexuality in ancient Greece and Rome are translated into modern, explicit English and collected together in this comprehensive sourcebook. Covering an extensive period, the volume includes writings by Plato, Sappho Aeschines, Catullus and Juvenal